Analysis Customer Relationship Management (CRM) for increase Competitive Advantage in Water Tourism “ Jiput ” Kediri City - Rahmadi, Afif Nur; Sandi Eka Suprajang; Alma Hariyati; Yulia Kristina (RISK : Jurnal Riset Bisnis dan Ekonomi, 2024)
T he purpose of this study is to evaluate the implementation of a CRM system can improve the visitor experience through personalization of service, rapid response to feedback, and better relationship management . Analyzing and describing Customer Relationship Management ( CRM ) can help in increasing Competitive Advantage in Water Tourism " Source Jiput . Research This using a qualitative descriptive approach and this approach emphasizes on detailed exploration and description of experiences and perspectives related to the implementation of CRM in Jiput Water Tourism. Data analysis uses data triangulation, where data triangulation is to cross-check and validate the results between one data and another data, both from secondary and primary data obtained in the field to be compared from selected data sources, then organized, analyzed, and concluded. From the results discussion the found that social media or digital marketing can used For promote and introduce A place tour for CRM manager is very necessary For manage tourists , so that traveler do visit back . Further support and mentoring are needed to ensure that each member can carry out their role effectively and show that Sumber Jiput is one of the most well-known tourist destinations in Kediri